Improving morphological awareness: Can direct instruction of morphological components and structures improve the quality of KS3 students’ writing in English? - Gilbert, L (2020)
Over the course of my teaching career, I have observed that in order to excel in English, the ability to expressively use a nuanced and wide vocabulary is fundamental. However, in my experience, many students’ expressive vocabulary knowledge is lacking, meaning that they cannot express themselves in writing with precision, or critique literature with the flair and nuance expected to access higher attainment scores and grades. Students’ work often relies on the use of the same turns of phrases or repeated sentence stems which have been taught as scaffolds and thus when writing, these stock phrases limit the students’ ability to creatively express themselves or their literary interpretations. In order to address this, my research explores the use of morphology as a means to unlock access to a wider range of vocabulary for students to use in their writing and to improve their knowledge of the way morphological components work in order to foster ‘word consciousness’ (Graves, 2016). Carlisle et al (2010) maintain that there has been a ‘growing interest in the role of morphological awareness in literacy acquisition’ (p. 464) but at the same time it is clear that the role that vocabulary, and I would argue specifically knowledge of the morphological components of English plays in the quality of students’ written compositions has received little attention particularly in the secondary school context (Olinghouse & Wilson, 2013).